1985
DOI: 10.1152/jappl.1985.59.6.1995
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylthiourea consumption reflects H2O2 concentrations and severity of acute lung injury

Abstract: Even though dimethylthiourea (DMTU) effectively scavenges O2 metabolites in vitro, it is often unclear if scavenging of O2 metabolites is the mechanism by which DMTU decreases tissue injury in biological models. Since DMTU not only scavenges O2 metabolites but is also consumed in a dose-response manner following reaction with hydrogen peroxide (H2O2) in vitro, we wondered whether DMTU would also be consumed by O2 metabolites in biological systems and if DMTU consumption would then reflect O2 metabolite concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…We also tested 150 mg/kg NAC administered topically and concomitantly with the allergen, in the same intratracheal 60 μl bolus with BPEx. The antioxidant DMTU, a potent scavenger of oxygen metabolites (21,22), was alternatively administered i.p. at a dose of 100 mg/kg in 0.5 ml sterile PBS (pH 7.2), as previously described to prevent chlorine oxidant-induced lung injury (23) (control animals received 0.5 ml of sterile PBS).…”
Section: Methodsmentioning
confidence: 99%
“…We also tested 150 mg/kg NAC administered topically and concomitantly with the allergen, in the same intratracheal 60 μl bolus with BPEx. The antioxidant DMTU, a potent scavenger of oxygen metabolites (21,22), was alternatively administered i.p. at a dose of 100 mg/kg in 0.5 ml sterile PBS (pH 7.2), as previously described to prevent chlorine oxidant-induced lung injury (23) (control animals received 0.5 ml of sterile PBS).…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose we used dimethylthiourea (DMTU), an oxygen metabolite scavenger [10], that is highly cell-permeable [11-13]. We also wished to examine the effects of Cl 2 on markers of oxidative stress and whether DMTU attenuated these effects.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that dimethyl-thiourea, mercaptopropionyl-glycine, and other SH-containing compounds can also inactivate the powerful oxidant hypochlorous acid [41][42][43]. Furthermore, dimethyl-thiourea is also an effective scavenger of hydrogen peroxide [44], and it has recently been shown to protect cardiac myocytes from hypoxic injury by inhibition of Na÷-Ca 2÷ exchange, and not by its antioxidant effects [45].…”
Section: Discussionmentioning
confidence: 99%